(untitled) (The International Journal for Scientific Research, 2024)
Most of those working in counseling and therapeutic services seek to focus their work with trauma survivors on the negative consequences of trauma; As post-traumatic stress disorder, anxiety, depression and addiction, and with the emergence of positive psychology and the concept of post-traumatic growth, a shift in the field of trauma research has been from focusing on negative outcomes to focusing on positive outcomes of trauma, where attention has been paid to positive changes or transformations that occur in the individual after exposure to trauma; Which became known as post-traumatic growth. Despite the important results of this approach in Counseling and therapeutic interventions and in research; However, this direction appears to be relatively unknown in the Arab countries particular by workers in the field of counselling and psychotherapy; Whereas the focus on negative outcomes and mitigating them is still the dominant approach. In this research, the researcher attempts to clarify the concept of post-traumatic growth, its fields and dimensions, and some of the fallacies that misunderstand it, distinguishing it from resilience and a sense of cohesion, with the aim of providing scientific material that motivates graduate students and researchers to pay attention to studying and understanding it in order to benefit from it in the context of the difficult reality experienced by some Arab societies and the societies whose members are exposed to many traumas.